The Implementation of Concept Map Method in Improving Learning Outcomes of Islamic Education at SMP Muhammadiyah 16 Lubuk Pakam - Nazwar Ali (Indonesian Journal of Education and Mathematical Science, 2022)
Teachers are the main and very important component in education and determine the success or failure of achieving goals in the learning process. The selection of appropriate learning methods is something that must be considered by the teacher. Based on this, research was conducted on the implementation of the Concept Map method. The formulation of the problem in this study is how the learning outcomes of Islamic Education of students before using the Concept Map method, how the process of implementing learning using the Concept Map method, and how the learning outcomes of Islamic Education of students after using the Concept Map method in class VIII SMP Muhammadiyah 16 Lubuk Pakam. The main purpose of this study was to determine the learning outcomes of 8th grade students of SMP Muhammadiyah 16 Lubuk Pakam by using the Concept Map method. This study used classroom action research which was carried out for two cycles. Data collection procedures were through student learning outcomes tests. Overall, the results of research that took place over two cycles showed that learning by using the Concept Map method based on the results of the data obtained, showed that in cycle I the learning outcomes of students had an average score of 71.11 (48.14%) and there was an increase in cycle II with an average score of 82.22 (85.18%). The Learning by using the Concept Map method has a significant change in the learning outcomes of students.